Anti-idiotypic Antibodies against BP-IgG Prevent Type XVII Collagen Depletion - Kamaguchi, Mayumi; Iwata, Hiroaki; Mori, Yuiko; Toyonaga, Ellen; Ujiie, Hideyuki; Kitagawa, Yoshimasa; Shimizu, Hiroshi (Frontiers in Immunology, 2017)
Bullous pemphigoid (BP) mainly targets type XVII collagen (COL17). Intravenous immunoglobulin (IVIg) is used to treat numerous autoimmune diseases, including BP. The major mechanism of action for IVIG is thought to be its immunomodulatory effect. However, little is known about the precise mechanisms of IVIg in BP. We investigate the cellular effects of IVIg, towards treatments for BP. Keratinocytes were treated with IgG from BP patients (BP-IgG) and with IVIg, and then the COL17 expression was detected by Western blotting. Cell adhesion and ex vivo dermal-epidermal separation were also investigated for the condition with BP-IgG and IVIg. BP-IgG targeting the NC16A domain induces the depletion of COL17 in cultured keratinocytes (DJM-1 cells). The COL17 levels in DJM-1 cells were decreased by 50% after 4 hours of BP-IgG stimulation as determined by Western blotting. In contrast, BP-IgG with IVIg was found to result in 70 to 90% increases in COL17 and to restore adhesion to the plate. Interestingly, IVIg significantly inhibited the binding of BP-IgG to the COL17-ELISA plate, and this was due to anti-idiotypic antibodies against BP-IgG. When anti-idiotypic antibodies against BP-IgG in 0.02% of IVIg were depleted from IVIg, those antibodies did not exhibit inhibitory effects on COL17 depletion. When cryosections of human skin were incubated with BP-IgG in the presence of leukocytes, dermal-epidermal separation was observed. BP-IgG treatment with IVIg or anti-idiotypic antibodies did not induce such separation. These findings strongly suggest the presence of anti-idiotypic antibodies against anti-COL17 IgG in IVIg. This mechanism of IVIg could be a target for therapies against BP.